1999
DOI: 10.1016/s0022-2275(20)33480-5
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of HDL by CETP in vivo and by CETP and hepatic lipase in vitro results in enhanced uptake of HDL CE by cells expressing scavenger receptor B-I

Abstract: The transport of HDL cholesteryl esters (CE) from plasma to the liver involves a direct uptake pathway, mediated by hepatic scavenger receptor B-I (SR-BI), and an indirect pathway, involving the exchange of HDL CE for triglycerides (TG) of TG-rich lipoproteins by cholesteryl ester transfer protein (CETP). We carried out HDL CE turnover studies in mice expressing human CETP and/or human lecithin:cholesterol acyltransferase (LCAT) transgenes on a background of human apoA-I expression. The fractional clearance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(26 citation statements)
references
References 42 publications
1
21
0
4
Order By: Relevance
“…Smaller HDL particles have been shown to be cleared more rapidly from the circulation than normal HDL particles, thereby decreasing circulating HDL levels. 30,[44][45][46][47] Smaller cholesterol-depleted HDL particles also appear to be less able to carry out the anti-atherogenic functions of HDL, including antioxidant and anti-inflammatory activities and protection against cellular accumulation of cholesterol in the arterial wall. 48,49 In the case of LDL, smaller LDL particles are less readily able to bind to hepatic LDL receptors, the efficient mechanism of LDL particle clearance, thereby raising circulating LDL levels.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller HDL particles have been shown to be cleared more rapidly from the circulation than normal HDL particles, thereby decreasing circulating HDL levels. 30,[44][45][46][47] Smaller cholesterol-depleted HDL particles also appear to be less able to carry out the anti-atherogenic functions of HDL, including antioxidant and anti-inflammatory activities and protection against cellular accumulation of cholesterol in the arterial wall. 48,49 In the case of LDL, smaller LDL particles are less readily able to bind to hepatic LDL receptors, the efficient mechanism of LDL particle clearance, thereby raising circulating LDL levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, catalytically inactive HL reduced HDL-C and apoA-I (ϳ30%, did not reach statistical significance) in Ldlr Ϫ/Ϫ mice on a chow diet but had no effect on these levels in Ldlr Ϫ/Ϫ mice on a Western diet. The catalytically inactive HL could affect HDL levels of the chow-fed mice by serving as a ligand, concentrating the particles at the cell surface and facilitating direct uptake (via HSPG-syndecan-1) (28,41,42) or selective uptake mediated by the B1 scavenger receptor (43,44). It is conceivable that the absence of reduced HDL levels in Western diet-fed mice reflects displacement of HDL from HL S145G by high levels of apoB-containing lipoproteins, as has been described for the homologous enzyme lipoprotein lipase (45).…”
Section: Discussionmentioning
confidence: 99%
“…HL bound to proteoglycan sulfate at hepatocytes promotes the selective uptake of HDL CE by a number of mechanisms (14), including via the SR-B1 receptor (23,27). Indeed, Collet et al (12) demonstrated that HDL CE uptake in vitro is enhanced in TGenriched human HDL upon treatment with HL.…”
Section: Discussionmentioning
confidence: 99%
“…1 To whom correspondence should be addressed at Toronto General Hospital, 200 Elizabeth St., Room EN11-229, Toronto, Ontario, Canada M5G 2C4. e-mail: gary.lewis@uhn.on.ca HDL isolated from CE transfer protein (CETP)/apoA-I transgenic mice showed a significant increase in SR-B1mediated HDL CE uptake in Chinese hamster ovary cells compared with control HDL isolated from apoA-I transgenic mice (12). The authors of the second study attributed the increase in HDL CE uptake to remodeling of HDL by CETP-mediated CE-TG interchange.…”
mentioning
confidence: 99%